PENERAPAN STRATEGI TRANSFORMASI GENERASI PENERUS 3 UNTUK MENYELAMATKAN PERUSAHAAN KELUARGA DARI KEBANGKRUTAN (STUDI KASUS PADA PT. DANLIRIS) - Istiatin Istiatin; Burhanudin Achmad Yani (STIE Pelita Nusantara Semarang, 2017)
Transformation is a process that must be applied to the family company in order to have a good business and family harmony. The purpose of this research is to analyze the third generation successor's characteristic, to know and understand the implementation of Transformation strategy and to know concretely the achievement of Generation Success 3 post implementation of Transformation strategy At PT Danliris.This research uses qualitative method, data collection is done by observation and approach of in-depth interview. Informant or resource is determined by purposive sampling. Then do the data validity by source triangulation method. Research results show that the next generation of PT Dan Liris who is currently the third generation has the expertise and responsibility in developing the company's business is supported by the courage and high creativity so that PT Dan Liris growing. The entire family of Dan Liris company is very much a successor because he is very appreciate and honor the predecessor as well as by applying the transformation of both structure, tehnology and people so until now the third successor has achievement, both business achievement by producing 4 subsidiaries and family harmony in the form of work conductivity shown by employees have high work motivation